The integrated modeling of microgrid cyber physical system based on hybrid automaton - Li, Peng; Zhang, Fan; Yang, Yi; Ma, Xiyuan; Yao, Senjing; Yang, Ping; Zhao, Zhuoli; Lai, Chun Sing; Lai, Loi Lei (Frontiers in Energy Research, 2022)
To fully reveal the interplay of the cyber system and physical system in the microgrid, this paper proposes a generic hierarchical modeling framework for cyber-physical integration modeling of microgrid, including two layers: physical device layer and controller layer. Each layer includes two parts: the continuous part (characterizing the physical system in the microgrid) and the discrete part (characterizing the cyber system in the microgrid). In this paper, firstly, detailed mathematical expressions describing the dynamic characteristics of each layer (including continuous characteristics and discrete characteristics) and describing the interplay of the continuous part and discrete part in each layer are given, which contributes to a better understanding of the interplay of the information flow and energy flow in the microgrid. Secondly, the cyber-physical integration modeling of each unit in the proposed framework is established using hybrid automata, which can clearly present the operation state of each unit of the microgrid and its state transfer process, which is beneficial to design the optimal operation state trajectory of the system. The proposed modeling framework is generic and can be extended to any dynamic system with cyber-physical integration. Finally, a typical microgrid system is taken as an example to verify the feasibility of the proposed modeling approach.